Crop Rotation for Reclaimed Ravine Lands - Gidwani, H.M.; Agarwal, M.C.; Dubey, L.N. (Journal of Soil and Water Conservation, 2022)
Five crop rotations were tried for finding out suitable crop rotation for reclaimed ravine areas. It was observed that Bajra +Arhar = Mustard is the best rotation and the increase in the yield of Bajra both grain and fodder is double that of Bajra continuous rotation. Bajra — Cowpea is the next best rotation. All the rotations tried buil t up soil fertility but Bajra +Arhar = Mustard followed by Bajra Cowpea are the best for this purpose. Hence Bajra +Arhar = Mustard and Bajra –Cowpea can be recommended as the best crop rotations for reclaimed ravine lands.